Genome sequence of Vibrio parahaemolyticus C5A causing acute hepatopancreatic necrosis disease in shrimp isolated from a Malaysian shrimp culture pond - Md. Ali, Amatul Samahah; Muthukrishnan, Sarmila; Nurhidayu, Al-saari; Mohd Ikhsan, Natrah Fatin; Saad, Mohd Zamri; Azmai, Mohamad Noor Amal; Yusof, Mohd Termizi; Md. Yasin, Ina Salwany; Tanaka, Mami; Mino, Sayaka; Sawabe, Tomoo (Elsevier, 2022)
We report the complete genome sequence of Vibrio parahaemolyticus strain C5A causing an acute hepatopancreatic necrosis disease (AHPND) in Penaeus vannamei sampled from a culture pond in the east of peninsular Malaysia isolated in 2017.